THE ADOPTION OF DIGITAL TEXTBOOKS IN DISTANCE LEARNING - Susilo, Adhi; Ahmad Suhardi, Deddy (Journal of Research and Innovation In Open and Distance Learning, 2024)
In recent years, the widespread adoption of digital textbooks has revolutionized the way students access educational content. Technology has advanced quickly, and as a result, textbooks are now available to students worldwide in digital form, which has improved their overall academic performance. This modification is acceptable for the sustainable learning program, where students have access to materials from anywhere and at any time and digital textbooks promote online learning. This study intends to examine the variables influencing elementary distance learner students’ intentions to adopt digital textbooks. Structured equation modeling (SEM) was used to evaluate quantitative data from 316 higher education students in Indonesia. According to the findings, students' intentions to use digital books were positively impacted by facilitating condition (Conway & Huffcutt), performance expectancy (PE), self-efficacy (SE), and perceived learning opportunities (PLO). However, attitude, affective, ICT usage habits, effort expectancy, and social influences did not affect students’ intention to use digital textbooks. This research provides important information for the government, decision-makers, and schools on using digital textbooks at the tertiary level in the future.